Myringoplasty and Myringoplasty with Cortical Mastoidectomy in Dry Ear: 60 Comparison of Surgical Outcome (Bangladesh Journal of Otorhinolaryngology, 2025)
Background: Chronic suppurative otitis media (CSOM) is one of the most common diseases of younger age in middle class population of the developing countries which causes significant impact in speech, cognitive, educational and psychological development in children and hearing impairment and recurrent ear discharge in adult.Aim: To identify the difference of graft take rate and hearing gain in the treatment of CSOM by myringoplasty and myringoplasty with cortical mastoidectomy in dry ear.Methods: Randomized controlled trial was conducted in the Department of Otolaryngology – Head & Neck Surgery, Dhaka Medical College Hospital, Dhaka from July 2018 to December 2019 with 54 patients having inactive mucosal COM. Total 54 patients age ranging from 15 to 55 years were taken. Group A: 27 of the patient were done myringoplasty and Group-B: 27 patient were done myringoplasty with cortical mastoidectomy. Postoperative follow up was given on 7th day, 2 weeks, 6 weeks and 3 months postoperatively. PTA was done to every patient 3 months postoperatively and hearing gain was compared between two groups.Results: Graft take rate was 22(81.48%) and hearing gain was 8.48(±6.83) dB in 27 patients of group-A and 24(88.89%) and 10.61 (±12.25) dB respectively in 27 patients of group-B. No statistically significant difference was found between two groups.Conclusion: Cortical mastoidectomy performed in inactive mucosal COM in this study gives no statistically significant benefit over myringoplasty alone as regards graft take rate and hearing improvement.Bangladesh J Otorhinolaryngology 2024; 30 (2): 58-67